(untitled) (International Scientific Journal Alfraganus, 2026)
Teaching competences take many forms and vary in content depending on the environment and subject area. As a result, English language teachers need to simplify and systematize their teaching competences to a certain extent. This article defines these competences in a broad sense, including teaching, students and learning, language and culture, educational institutions, society, and professional life.